Investigating the Effectiveness of Mindfulness Training on Sustained Attention, Self-Control, and Cognitive Flexibility in Children with Attention Deficit Hyperactivity Disorder (ADHD) - Moeini Saleh, Mahboobeh; Amini, Naser; Keykhosravani, Moloud (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the effectiveness of mindfulness training on sustained attention, self-control, and cognitive flexibility in children diagnosed with Attention-Deficit/Hyperactivity Disorder (ADHD). Methods and Materials: The research employed a quasi-experimental design with a pretest–posttest–follow-up structure and a control group. A sample of 30 male students aged 8 to 12 years with a clinical diagnosis of ADHD was selected through purposive sampling from a private clinical population. Participants were randomly assigned to experimental (n=15) and control (n=15) groups. The experimental group received an 8-session mindfulness training protocol, each session lasting 90 minutes, based on developmentally appropriate exercises. Outcome measures included the Self-Control Scale (Tangney et al., 2004), the Continuous Performance Test (Rosvold et al., 1965) for sustained attention, and the Wisconsin Card Sorting Test (Grant & Berg, 1984) for cognitive flexibility. Data were collected at three time points: pretest, posttest, and a two-month follow-up, and analyzed using repeated measures ANOVA. Findings: Results showed significant group-by-time interaction effects for all three outcome variables (p < .001). Self-control scores increased significantly in the experimental group from pretest to posttest and remained stable at follow-up. Measures of sustained attention improved significantly, as evidenced by reductions in omission and commission errors and shorter reaction times (p < .001). Cognitive flexibility also showed statistically significant gains, with decreases in perseverative and total errors and increases in correct category classification (p < .001). Bonferroni post hoc tests confirmed that most improvements persisted at follow-up, indicating durable intervention effects. Conclusion: Mindfulness training is an effective and sustainable intervention for improving executive functions—specifically self-control, sustained attention, and cognitive flexibility—in children with ADHD, offering a promising non-pharmacological treatment pathway.